A turn-on fluorescence strategy for cellular glutathione determination based on the aggregation-induced emission enhancement of self-assembled copper nanoclusters. Issue 21 (1st September 2020) - Wang, Hai-Bo; Mao, An-Li; Gan, Tian; Liu, Yan-Ming
Abstract : A turn-on fluorescence method has been designed for the determination of cellular GSH levels based on the controlled aggregation-induced emission enhancement of self-assembled CuNCs. Abstract : As a class of ideal fluorescent nanomaterials, self-assembled copper nanoclusters (CuNCs) have attracted increasing interest. Unfortunately, most of these CuNCs only possessed bright luminescence in acidic solution, which limited their practical applications in a physiological environment. Retaining the strong fluorescence of these CuNCs in neutral or alkaline solution is still a challenging task. In this strategy, self-assembled CuNCs were prepared by using 4-methylthiophenol as the protecting ligand. The self-assembled CuNCs display stable and bright luminescence with excitation/emission maxima at 330/605 nm even in neutral and alkaline environments. Interestingly, with the addition of glutathione (GSH), the fluorescence intensity of CuNCs is enhanced strongly through the GSH-controlled aggregation-induced emission enhancement of self-assembled CuNCs. The turn-on fluorescence strategy can determine the GSH concentration in the range from 1 to 100 μM with a limit of detection of 300 nM. In addition, the method is employed for the determination of GSH levels in cells. Therefore, the turn-on fluorescence strategy is reliable, sensitive and suitable for the determination of cellular GSH levels.